The Effect of Red Spinach Juice on Hemoglobin Levels in Pregnant Women: A Randomized Controlled Trial - Endang Sari; Mekar Zenni Radhia; Hanifa Zaini S (Sriwijaya Journal of Obstetrics and Gynecology, 2025)
Introduction: Iron deficiency anemia is a prevalent health concern among pregnant women globally, including Indonesia. Red spinach (Amaranthus tricolor), rich in iron and other nutrients, holds promise as a natural intervention. This randomized controlled trial aimed to investigate the efficacy of red spinach juice in improving hemoglobin levels in pregnant women in West Sumatra. Methods: This study enrolled 180 pregnant women (18-35 years) with mild anemia (hemoglobin 10.0-10.9 g/dL) in their second trimester. Participants were randomly assigned to either the intervention group (daily red spinach juice, 200 mL) or the control group (standard iron supplementation) for eight weeks. Hemoglobin levels were measured at baseline, week four, and week eight. Results: A significant increase in hemoglobin levels was observed in both groups (p < 0.001). However, the intervention group exhibited a greater mean increase in hemoglobin (1.8 g/dL) compared to the control group (1.2 g/dL) at week eight. There were no significant differences in adverse events between the groups. Conclusion: Red spinach juice demonstrates potential as an effective adjunct or alternative to standard iron supplementation in improving hemoglobin levels in pregnant women with mild anemia. Further research is warranted to confirm these findings and investigate long-term effects.